Situ preparation of N-ZnO/graphene nanocomposites: excellent candidate as a photocatalyst for enhanced solar hydrogen generation and high performance supercapacitor electrode - Bhirud, Ashwini P.; Sathaye, Shivaram; Waichal, Rupali; Park, Chan-Jin; Kale, Bharat (Journal of Materials Chemistry A, 2015)
We have demonstrated a facile in situ wet chemical method to synthesize nanostructured nitrogen doped ZnO/Graphene (N-ZnO/GR) nanocomposites for the first time. Nitrogen doped ZnO over graphene (N-ZnO/GR) was studied using various concentrations of graphene. During the synthesis of N-ZnO/GR nanocomposites, in situ formation of graphene via GO reduction and formation of 4-9 nm N-ZnO have been demonstrated. The composite N-ZnO/GR absorbs in the visible region and this property is used for the photocatalytic reaction to transform hazardous H2S waste into eco-friendly hydrogen using solar light. The N-ZnO/GR nanocomposite with 0.3% graphene exhibits an enhanced photocatalytic stable hydrogen production rate i.e. similar to 5072 mu mol h(-1) under visible light irradiation. It is noteworthy that the N-ZnO/GR electrode exhibits a high specific capacitance of 555 F g(-1) and excellent cyclic performance with nearly 96.20% capacity retention after 2000 cycles at a current density of 10 A g(-1). These results indicate great potential applications of N-ZnO/GR in developing high hydrogen production and supercapacitors with high energy and power densities.

Evaluation of humidity sensor based on PVP-RGO nanocomposites - Bhangare, Bhagyashri; Jagtap, Shweta; Ramgir, Niranjan; Waichal, Rupali; Muthe, K. P.; Gupta, S. K.; Gadkari, Sanjay C.; Aswal, D. K.; Gosavi, Suresh (IEEE sensors journal, 2018)
his paper describes the humidity sensing properties of one step in situ synthesized poly (N-vinyl pyrrolidone)- reduced graphene oxide (PVP-RGO) nanocomposites. Different PVP-RGO nanocomposites were obtained by varying PVP/GO weight %ratio as x/50 mg, wherein x = 25, 50, and 75 mg, respectively. The real-time adsorption kinetics of the water molecules during the humidity sensing were also discussed using Elovich model, pseudo first and second order equations. The increase in humidity response of 1.5 PVP-RGO nanocomposite is attributed to the presence of large amount of oxygen functionalities. The above observation was corroborated using spectroscopic analysis. The optimized PVP-RGO nanocomposite showed faster response kinetics with response and recovery times of 10 and 20 s, respectively. The present humidity sensor shows remarkable linearity over the range of 20-90%RH. More specifically, sensitivity was correlated with oxygen functionalities created due to variation of PVP during the functionalization of RGO nanosheets.

Nonenzymatic glucose detection in human serum using Ni nanoparticles decorated reduced graphene oxide - Waichal, Rupali; Bhirud, Ashwini; Fouad, H.; Gosavi, Suresh; Ashokkumar, Muthupandian (Science of Advanced Materials, 2020)
Reduced Graphene oxide (RGO) decorated with Ni nanoparticles (NiNPs) composites, have been successfully synthesized using a simple hydrothermal method and possessing excellent electrocatalytic activity towards glucose oxidation. The morphological and structural features of RGO-Ni nanocomposites were characterized by field emission scanning electron microscopy (FESEM), transmission electron microscopy (TEM), X-ray diffraction (XRD), Raman spectroscopy, X-ray photoelectron spectroscopy (XPS) and energy dispersive spectroscopy (EDS). From TEM, we observed that NiNPs were anchored on RGO sheets. Cyclic Voltammetric (CV) study revealed that the electrocatalytic activity of RGO-Ni nanocomposite with 20% Ni loading (RGONi-20) towards glucose oxidation is better than that shown by bare Glassy Carbon Electrode (GCE), RGO, bare NiNPs, RGONi10 and RGONi-30. The prepared nanocomposites exhibited fast electrocatalytic response (<5 s) towards glucose oxidation. Amperometric study indicates that the present glucose sensor have exhibited excellent performance by offering a lowest detection limit as 5.1 mu M, with linier range from 2 to 5000 mu M and high sensitivity of 896.67 mu A mM(-1) cm(-2). Interference from different anticipatable electroactive substances such as ascorbic acid (AA), uric acid (UA) and dopamine (DA) is not observed. Furthermore, the application of the as prepared sensor was successfully demonstrated for the detection of glucose in human serum and results were comparable to presently used nonenzymatic technique. RGONi-20 nanocomposite electrode holds great promise for the development of biosensors and other electrochemical devices.
Keywords: Electrochemical; Glucose Sensor; Graphene-Nickel Nanoparticles; hydrothermal; Nanocomposite; Nonenzymatic